Single primer pair for amplifying segments of distinct Shiga-like-toxin genes by polymerase chain reaction. - Karch, H (1989)
By using a single synthetic oligonucleotide primer pair in the polymerase chain reaction, we amplified specific Shiga-like-toxin (SLT) gene segments from DNAs of 20 clinical Escherichia coli isolates, irrespective of whether they produce SLT-I, SLT-II, or heretofore uncategorized SLTs. These segments were not detectable in any of 20 nontoxigenic E. coli strains. The primers deduced from a conserved region among SLT genes are so-called degenerate-sequence primers; i.e., they contain intentionally introduced sequence ambiguities to overcome minor sequence variations within different SLT genes. In direct gel hybridization with genomic DNA, both primers recognized SLT-I and SLT-II DNA sequences. Amplified sequences of target DNA obtained by polymerase chain reaction were visualized after gel electrophoresis by ethidium bromide staining, and definitive identification of the amplification product as an SLT gene segment was achieved by hybridization to SLT-I- and SLT-II-specific 20-base oligonucleotide probes complementary to a portion of the amplified sequences but not to the primers. The detecting oligonucleotide probes shared only 30% base homology and were shown to recognize specifically SLT-I or SLT-II sequences within genomic DNA. Moreover, they were used to distinguish whether the amplified sequence originated from SLT-I or SLT-II genes. The PCR system with the primers described here is a powerful technique to amplify SLT sequences in E. coli strains that produce serologically distinct SLTs and will facilitate identification of these pathogens, particularly among a multitude of nonpathogenic E. coli strains.